Tradução de poesia concreta do português para a Libras: transcriando um poema de Paulo Leminski - Sena, Juliana Perim (Universidade Federal de São Carlos, 2018)
Bearing in mind: A) the challenges inherent in the translation of poetry due to its condition as an aesthetic object; B) the specificities involved in the activity of mobilizing speeches of a linguistic pair that contains linguistic modalities (oral-auditory and visual-gestural-spatial) and different semiotic translation supports - Portuguese written language and Brazilian Sign Language (Libras); and, C) the characteristics of Concrete Poetry, mainly with regard to the use of the graphic space of the page as a structural agent, this work presents a practical proposal of transcreation (in the Haroldian conception), in the Portuguese Language> Brazilian Sign Language direction, for the poem 'metamorphosis' by Paulo Leminski. To substantiate the proposal and reflections, authors like Bakhtin (1988) are placed in dialogue; Barros (2015); Campos (2013); Campos, Campos and Pignatari (1975); Segala (2010), among others. To create the parallels in the poem in Libras, a varied set of strategies was used, with verbal and non-verbal resources, from linguistic and discursive strategies to video editing semiotics, such as: phonological-lexical organization, use of expressions facial and body, speed and rhythm of signaling, acceleration and reduction of speed through editing, color change of the image, application of image effects, among other resources. It is believed that the research contributes, above all, to the discussions and reflections it raises about the influences of intermodality and intersemiosis in the transcriatory activity of concrete poetry for Libras, showing the creative character of the translator and the power of the concept of transcreation in this context. The work can also contribute to foster the production of translation materials of artistic and cultural content in the Portuguese - Libras direction, favoring the realization of the right of linguistic accessibility of Brazilian deaf communities to these Portuguese language contents and, consequently, contributing to cultural exchange between speakers of the two languages ​​involved. Finally, it is also justified because it constitutes a “fertile ground” for thinking about issues that disturb students of translation practice, such as fidelity, untranslatability and authorship.
Translation of concrete poetry from Portuguese to Libras: transcribing a poem by Paulo Leminski
Keywords: Libras; Poesia concreta; Transcriação; Haroldo de Campos; Leminski; LINGUISTICA, LETRAS E ARTES